Integrating Transformational Leadership And Job Analysis To Optimize Structural Staff Placement: A Systematic Literature Review - kholish atikah Azzam; ansarul fahrudda (Global Journal of Health Administration, 2026)
Abstract Background : Human resource (HR) management in hospitals faces competency mismatches in structural positions and disproportionate workloads. This phenomenon stems from weak organizational needs analysis and flawed bureaucratic structures. Aims : This study aims to provide a novel descriptive theoretical framework on the "right man on the right place" concept and work standards through a needs analysis approach and proper organizational structure design to generate accurate job descriptions.. Methods : This Systematic Literature Review utilized the PRISMA protocol. A comprehensive literature search was conducted on Google Scholar, PubMed, and ScienceDirect databases for the 2020-2026 period. Results : The synthesis indicates that unclear main duties and functions trigger multiple roles due to administrative staff shortages. Implementing job analysis competencies supported by transformational leadership proves to be a key factor in enforcing fair workload distribution. The use of instruments like Workload Indicators of Staffing Need (WISN) is effective in ensuring proper staff placement. Conclusion : The application of transformational leadership in strengthening organizational structure through the integration of job analysis and objective workload calculation is an absolute pillar to minimize human error and optimize patient care quality in hospitals. Keywords : Job Analysis, Patient Care Quality, Staff Placement, Structural Position, Transformational Leadership.   Abstrak Latar Belakang : Manajemen sumber daya manusia (SDM) di rumah sakit dihadapkan pada terjadinya ketidaksesuaian kompetensi pada jabatan struktural serta beban kerja yang tidak proporsional. Fenomena ini berakar dari kelemahan analisis kebutuhan organisasi dan struktur birokrasi yang keliru. Tujuan : Penelitian ini bertujuan untuk memberikan deskripsi teoretis baru mengenai konsep the right man on the right place dan standar kerja melalui pendekatan analisis kebutuhan serta desain struktur organisasi yang benar guna menghasilkan deskripsi pekerjaan (job description) yang akurat. Metode : Tinjauan literatur sistematis (Systematic Literature Review) ini mengikuti protokol PRISMA. Pencarian artikel dilakukan pada database Google Scholar, PubMed, dan ScienceDirect untuk periode 2020-2026. Hasil : Sintesis hasil menunjukkan bahwa penataan tugas pokok dan fungsi yang tidak jelas memicu fenomena peran ganda (multiple roles) akibat kekurangan staf administrasi. Implementasi kompetensi analisis jabatan yang didukung oleh kepemimpinan transformasional terbukti menjadi kunci utama penegakan keadilan distribusi beban kerja (work load). Kesimpulan : Penerapan kepemimpinan transformasional dalam penguatan struktur organisasi melalui integrasi analisis jabatan dan penghitungan beban kerja yang objektif merupakan pilar mutlak untuk meminimalkan human error dan mengoptimalkan mutu pelayanan pasien di rumah sakit.. Kata Kunci : Analisis Jabatan, Jabatan Struktural, Kepemimpinan Transformasional, Mutu Pelayanan Rumah Sakit, Penempatan Staf.